A fluorescent probe for detection of Hg2+ ions constructed by tetramethyl cucurbit[6]uril and 1,2-bis(4-pyridyl)ethene - Chen, Xiaoqian; Yang, Naqin; Ma, Yue; Yang, Xinan; Ma, Peihua (Beilstein Journal of Organic Chemistry, 2023)
In this paper, tetramethyl cucurbit[6]uril (TMeQ[6]) and 1,2-bis(4-pyridyl)ethene (G) were used to construct a supramolecular fluorescent probe G@TMeQ[6]. The host–guest interaction between TMeQ[6] and G was investigated using 1H NMR spectroscopy, single-crystal X-ray diffraction and various experimental techniques. The results show that TMeQ[6] and G form an inclusion complex with a host–guest ratio of 1:1 and the equilibrium association constant (Ka) was 2.494 × 104 M−1. The G@TMeQ[6] fluorescent probe can sensitively recognize Hg2+ ions by fluorescence enhancement. The linear range is 0.33 × 10−5–1.65 × 10−5 mol·L−1, R2 = 0.9926, and the limit of detection is 4.12 × 10−8 mol·L−1. The fluorescent probe can be used to detect the concentration of Hg2+ ions in aqueous solution, and provides a theoretical basis for the development of new fluorescent probes for detecting heavy metal ions.
Keywords: 1,2-bis(4-pyridyl)ethane; fluorescent probe; Hg2+ ion recognition; host–guest chemistry; tetramethyl cucurbit[6]uril